A scoping review of post-school young adults with mild-moderate intellectual disabilities employment retention within the open labour market in low- and middle income countries - Danster, Dylan (Division of Occupational Therapy, 2025)
Background: Employment is a critical milestone for adults with intellectual disabilities, yet young adults with intellectual disabilities in low- and middle-income countries (LMICs) face significant challenges in entering and retaining employment in the open labour market. Extensive research in high-income countries highlights the opportunities and ability of individuals with intellectual disabilities to secure employment in the open labour market. Further research focused on the retention of such employment in LMICs is needed. Objectives: This scoping review aims to explore existing research on how young adults with intellectual disabilities retain employment in LMICs, identifying key factors, barriers, and facilitators influencing retention. Method: The review uses the methodological framework of Arksey and O'Malley, along with updates by Levac and colleagues and the PRISMA-ScR guidelines (Arksey and O'Malley, 2005; Levac, Colquhoun & O' Brien, 2010). The PRISMA-ScR (Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews) guidelines are premised on the framework devised by Arksey and O'Malley (2005) for specifically conducting scoping reviews. The framework outlines a five-stage methodological approach, which is listed as: 1) identifying the research question, 2) identifying relevant studies, 3) study selection, 4) Charting the data and 5) collating, summarising and reporting results. A comprehensive search of electronic databases from 1996-2024 yielded relevant primary studies in accordance with the inclusion criteria of the scoping review. The inclusion criteria identified studies conducted in low and middle-income countries (as defined by the World Bank); and involved a focus on post school young adults (aged 18-35) with mild to moderate intellectual disabilities. The relevant primary studies addressing employment retention within mainstream workplaces were considered and independently screened through a structured two-level screening process against the inclusion and exclusion criteria by two qualified occupational therapists using the Rayyan web App. The Rayyan web-based application is designed to streamline a collaborative review process by assisting researchers in screening and selecting the studies for systematic and scoping reviews (Ouzzani et al., 2016). During the first-level screening, titles and abstracts were independently reviewed by the two reviewers to identify studies meeting the predefined inclusion criteria, with Rayyan's blinding feature minimising bias. Irrelevant studies were excluded, and potentially relevant or unclear studies were transitioned to the next stage. In the second-level screening, full-text articles of studies identified in the first level were retrieved and thoroughly reviewed to confirm eligibility. Discrepancies between 2 reviewers were resolved through an iterative discussion process with a third reviewer. The web app's tools for labelling and categorising studies ensured a systematic decision-making and transparent documentation throughout the reviewing process. Results: The analyses of the four included studies highlighted key practices which were grouped under two major themes. The themes were: The critical facilitatory role of the occupational therapist and the contribution of disability related legislation and policy. These themes described how work preparation programmes, disability awareness training, advocacy for inclusive laws, and employment incentives contributed to the retention of young adults with mild-moderate intellectual impairment in open labour market employment. Gaps in research, particularly around unique stressors faced by individuals in LMICs, were noted. Conclusion: This review underscores the need for targeted interventions, including the expansion of inclusive legislative frameworks, to improve employment retention for persons with intellectual disabilities in LMICs. Ultimately, this holds the potential for people with intellectual disabilities (PWID), as a vulnerable group to improve their employment outcomes, particularly in retaining their open labour market employment.